Endonasal orbitotomy as a first treatment for posttraumatic intraorbital hemorrhages in patients with frontal basilar trauma - О. D. Bondarchuk; I. V. Dmytrenko; N. D. Didyk; A. S. Isniuk (Ukrainian Society of Ophthalmologists, 2021)
Background: Intraorbital hemorrhages are one of the most dangerous complications of frontal bone trauma and frontal and orbital trauma because of the close and intricate anatomical relationships among the cranial cavity, orbit, nose and paranasal sinuses. Failure to solve the problem promptly will inevitably lead to disability. Effective treatment requires a multidisciplinary surgical team including a neurosurgeon, otorhinolaryngologist, ophthalmologist and a maxillofacial surgeon. Purpose: To assess the efficacy of endonasal endoscopic transethmoidal orbitotomy (TEO) and transcutaneous orbitotomy (TCO) in patients with post-traumatic intraorbital hemorrhages. Material and Methods: Fifteen patients (9 men and 6 women) with retrobulbar hematoma were included in this study. Patient age ranged from 33 years to 65 years. Of the 15 patients, 8 received endonasal endoscopic TEO and 7, TCO. Preoperatively, each patient underwent an eye examination, ultrasonography of the orbit, and spiral computed tomography of the paranasal and periorbital sinuses. Postoperative examinations were performed at 7 days and 1 month. Exophthalmos was assessed using a Hertel's exophthalmosmeter (ALMAS YZ9). Sivtsev-Golovin charts were used to assess visual acuity. Statistical analyses were conducted using Microsoft Excel and Statistica (StatSoft, Tulsa, OK, USA) software. Results: The preoperative exophthalmos was 18.5 ± 2.12 mm in patients scheduled for TEO and 16.9 ± 1.78 mm in those scheduled for TCO. On day 7 after surgery (the day of discharge), exophthalmos reduced to 6.4 ± 0.77 mm in patients undergoing TEO (p < 0.0005) and 8.8 ± 0.94 mm in those undergoing TCO (p < 0.005). The preoperative visual acuity (VA) was 0.07 ± 0.03 in patients scheduled for TEO and 0.09 ± 0.05 mm in those scheduled for TCO. On day 7, mean VA improved to 0.81 ± 0.12 (p < 0.00005) in patients undergoing TEO, and to 0.56 ± 0.34 in those undergoing TCO. The two groups showed practically the same pattern of a longitudinal decrease in chemosis. Diplopia in upward and downward gaze and any restriction in ocular motility disappeared in patients undergoing TEO by the day of discharge (day 7), which was 4-5 days earlier than in patients undergoing TCO, with a postoperative period 4.25 ± 0.75 days longer (p<0.05) in the latter patients. At one month, mean VA improved to 0.89 ± 0.08 (p < 0.00005) in patients of the TEO group, and to 0.75 ± 0.15 (p < 0.005) in patients of the TCO group. Conclusion: Endonasal endoscopic transethmoidal orbitotomy was significantly more advantageous than transcutaneous orbitotomy, with a faster recovery, particularly, shorter postoperative period, faster restoration of visual acuity and ocular motility, minimum trauma to soft orbital tissues, and no external damage to facial skin.